The Academic Profession in Europe: New Tasks and New Challenges
XVIII, 202 p.
Keywords: This book is the first of several with the results of a collaborative European project supported by the European Science Foundation on changes in the academic profession in Europe (EUROAC). It provides a short description of the ESF EUROHESC programme and the particular forms of international collaborative research projects which are funded under the umbrella of this programme. It then outlines the EUROAC project. This project has chosen three foci (governance, professionalisation, academic careers) to analyse changes in the work of the academic profession. The first results in the form of in-depth literature reviews constitute the content of the book. These eight literature reviews about the state of the art of existing research feature the various dimensions of the overall theme. A particular emphasis is put on factors leading to changes in the work tasks of the academic profession in Europe and how the academic profession is coping with these new challenges. Thus, the book provides a state of the art account of existing research about the following themes: main results of previous studies on the academic profession; the academic profession and their interaction with new higher education professionals; professional identities in higher education; extending work tasks: civic mission and sustainable development; academic careers in academic markets; the changing role of academics in the face of rising managerialism; the influence of quality assurance, governance, and relevance on the satisfaction of the academic profession. .